Journal Notes - various authors (GDR Bulletin, 1980)
Reviews of: Connaissance de la RDA (announcment of new journal) L80 Heft 13 and Spuren Vol. 2 (Geoffrey Davis) Neue Deutsche Literatur Vol. 28, No. 1-3 (Judith Cox)